SGS-LTER long-term monitoring project: arthropod pitfall trapping on small mammal trapping webs on the Central Plains Experimental Range, Nunn, Colorado, USA 1998-2006, ARS study number 118 - Stapp, Paul (Colorado State University. Libraries, 1998)
This data package was produced by researchers working on the Shortgrass Steppe Long Term Ecological Research (SGS-LTER) Project, administered at Colorado State University. Long-term datasets and background information (proposals, reports, photographs, etc.) on the SGS-LTER project are contained in a comprehensive project collection within the Repository (http://hdl.handle.net/10217/100254). The data table and associated metadata document, which is generated in Ecological Metadata Language, may be available through other repositories serving the ecological research community and represent components of the larger SGS-LTER project collection. With the exception of heteromyids, eg kangaroo rats and pocket mice, most small rodents in shortgrass steppe are omnivorous. Depending on season, arthropods (insects and arachnids) make up 40-85% of the diet of grasshopper mice and thirteen-lined ground squirrels, the most widespread rodents in northern shortgrass steppe. Small mammals are among the most important predators of ground-dwelling macroarthropods and herbivorous insects provide a direct resource link between weather and plant production. Understanding temporal variability in the abundance of arthropods is central to determining the mechanisms that drive small rodent populations. At present, there are no long-term studies of arthropods in shortgrass steppe, despite the important role that these taxa play in grassland food webs. Beginning in 1998, we implemented field protocols to track changes in relative abundance of terrestrial macroarthropods in grassland and shrub-dominated habitats of shortgrass steppe. Sampling was conducted on the six trapping webs (three upland prairie, three lowland saltbush) where we studied rodent populations, and was conducted approximately monthly from May-September (4-5 sessions/year). Ground-dwelling macroarthropods were sampled on each web using pitfall traps, set in one four-by-five grid, with 10 m between traps. Traps consisted of plastic cups (90-mm diameter, 120 mm deep), including a plastic funnel (90-mm diameter), buried flush with the ground surface. Traps were shaded with wooden covers held in place with nails; traps could be closed when not operational by nailing the cover flush to the ground. Traps were usually open for 4 consecutive days (ie 80 trap-days) during a trapping session. On the 4th day, captured arthropods were removed from the traps, identified and released. All arthropods were identified to the ordinal level; beetles (Coleoptera), crickets (Orthoptera), true bugs (Hemiptera) and spiders were identified to the familial level; and a few taxa, eg tenebrionid beetles, were identified to species. We also recorded any reptiles and amphibians captured. The number of individuals of each taxa captured per 100 trap-days was used as an index of relative abundance, with adjustments made for traps that were flooded or disturbed by cattle or for changes to the number of days that traps were open (range 4-7 days). We sampled grasshoppers by counting the numbers flushed from 0.78-m2 circular plots (hoops) placed on each web. Hoops were set out on the day that pitfall traps were opened and were surveyed on the day that traps were closed. A technician used a wooden lath to flush and count all grasshoppers from each hoop. Grasshoppers were not identified to species. Surveys were conducted in 1998, then were discontinued until 2002. In 1998 and from 2002-2005, nine hoops were sampled on each web. Beginning in 2006, we sampled a total of 20 hoops on each web.
The Short Grass Steppe site encompasses a large portion of the Colorado Piedmont Section of the western Great Plains. The extent is defined as the boundaries of the Central Plains Experimental Range (CPER). The CPER has a single ownership and landuse (livestock grazing). The PNG is characterized by a mosaic of ownership and land use. Ownership includes federal, state or private and land use consists of livestock grazing or row-crops. There are NGO conservation groups that exert influence over the area, particularly on federal lands.
Natural Resource Ecology Laboratory (NREL)
Shortgrass Steppe-Long Term Ecological Research (SGS-LTER)
Keywords: population dynamics; arthropods; plant animal interactions; community dynamics; populations; animals; invertebrates